Predatory evidence in the high-latitude cold-water gastropod Buccinanops deformis (King, 1832) from the Holocene littoral sand ridges, Argentina, SW Atlantic - Gómez Espinosa, Ma. Catalina (2018)
In this study investigates the predatory activity on a Holocene gastropod from the Argentinean Malacological Province. Buccinanops deformis (King, 1832), endemic in the southern hemisphere, is a typical taxon of cold-waters and high latitudes. We observed direct evidence of durophagy as lethal and sublethal damage. Sublethal damage was studied using traces of repaired shell as an indicator of activity by durophagous predators. Three parameters were used to evaluate durophagous predation: frequency of predation, repair scar frequency and prey effectiveness. A predatory-prey interaction was identified between Danielethus crenulatus (A. Milne-Edwards, 1879) and B. deformis during the Holocene on the Argentinean littoral coast. The low value observed for shell repair frequency (0.06), the low frequency of predation (0.16), and the intermediate value for prey effectiveness (0.37) may be interpreted because of a low but effective predatory activity.